Crystalline silica particles exposure modulated miRNA expression profiles in human macrophage-like THP-1 cells - Evangel Kummari; Birgitte Lindeman; Unni C. Nygaard; Tellef Helle-Valle; Manosij Ghosh; Peter H.M. Hoet; Hubert Dirven; Nur Duale (Toxicology, 2026)

E-cigarette Aerosol Containing Nicotine Increases Aortic Stiffness in Young Mice - Pireyatharsheny Mulorz; Joscha Mulorz; Agnesa Mazrekaj; Hsiang-Han Liu; Wiebke Ibing; Joshua M. Spin; Lasse Bach Steffensen; Hans C. Beck; Uwe Raaz; Kensuke Toyama; Hubert Schelzig; Philip S. Tsao; et al. (Cardiovascular Toxicology, 2026)

Experimental assessment of ambient gamma dose equivalent rates measured outdoors in the Republic of Benin from 2019 to 2020 - Arnaud A. Gbetchedji; Daniel S. Takou; N. Innocent Gbaï; Mahougnon B. Zinsou; Hubert C. Hounsossou; Thierry C. M. Medehouenou; Rodrigue S. Allodji (Environmental Monitoring and Assessment, 2026)

Immune profiling of human blood cells after indirect exposure to crystalline silica particles - Evangel Kummari; Anja Bråthen Kristoffersen; Sabin Bhandari; Hege Hjertholm; Hubert Dirven; Sarah E. Josefsson; François Huaux; Riccardo Leinardi; Cristina Pavan; Manosij Ghosh; Peter Hoet; Unni C. Nygaard; et al. (Environmental Research, 2026)

Multi-omic analysis of canine aging uncovers conserved aging pathways - Zane Koch; Jessica L. Graves; Steve Annan; Phillip A. Frankino; Michelle Nelson; James E. McMahon; Ashley P. Tovar; Hubert C. Chen; Celine-Lea Halioua-Haubold; Matthew Peloquin (GeroScience, 2025)
Aging is a complex biological process characterized by molecular changes across multiple biological scales. While these alterations have been extensively studied in humans and rodents, the molecular changes associated with aging in dogs remain underexplored despite their relevance as a model for human aging. In this study, we profiled gene expression ( n = 16,273 genes) and protein abundance ( n = 2041 proteins) in whole blood and blood plasma from 40 laboratory beagles across young (3–5 years old, n = 10), old (8–9 years old, n = 17), and geriatric (10–14 years old, n = 13) life stages. We identified 816 genes and 40 proteins that significantly changed in abundance during aging, converging on pathways involved in DNA repair, collagen processing, and inflammation. Notably, these canine aging signatures overlapped with human age-associated genes, including those tied to the hallmarks of aging, reinforcing the existence of conserved aging mechanisms across species.

Preaccretionary origin of clay minerals in CI chondritic objects? Insights from the Orgueil clay mineralogy and iron oxidation state - J.-C. Viennet; K. Amano; L. Delbes; B. Lavina; F. Hubert; S. Bernard; S. Yaroslavtsev; D. Bessas; A. Chumakov; J.-P. Celse; M. Gounelle; L. Remusat; et al. (Earth and Planetary Science Letters, 2025)

The Martian oxygen green line dayglow: response to solar activity - L. Soret; H. Robin; J.-C. Gérard; L. Gkouvelis; I. Thomas; B. Ristic; Y. Willame; B. Hubert; A.C. Vandaele; J.P. Mason; F. Daerden; M.R. Patel (Icarus, 2025)

A Comparison of Dietary Intake Among Rural Americans With and Without Diabetes - Christian A. Koziatek; Melissa Rony; Carolina Quintero Arias; Tammy Flores; Matthew Heider; Molly Smith; Sadakat Chowdhury; Haley Motola; Jill Hubert-Simon; Karen Holden; David C. Lee (Journal of Nutrition Education and Behavior, 2025)

Inversion of ultraviolet occultation profiles in a dusty atmosphere: Analytic and numerical methods - B. Hubert; L. Soret; J.-C. Gérard; G. Wautelet; G. Munhoven; A. Piccialli; A.-C. Vandaele (Icarus, 2025)

Novel oil‐associated bacteria in Arctic seawater exposed to different nutrient biostimulation regimes - Francisco D. Davila Aleman; María A. Bautista; Janine McCalder; Kaiden Jobin; Sean M. C. Murphy; Brent Else; Casey R. J. Hubert (Environmental Microbiology, 2024)
The Arctic Ocean is an oligotrophic ecosystem facing escalating threats of oil spills as ship traffic increases owing to climate change‐induced sea ice retreat. Biostimulation is an oil spill mitigation strategy that involves introducing bioavailable nutrients to enhance crude oil biodegradation by endemic oil‐degrading microbes. For bioremediation to offer a viable response for future oil spill mitigation in extreme Arctic conditions, a better understanding of the effects of nutrient addition on Arctic marine microorganisms is needed. Controlled experiments tracking microbial populations revealed a significant decline in community diversity along with changes in microbial community composition. Notably, differential abundance analysis highlighted the significant enrichment of the unexpected genera Lacinutrix , Halarcobacter and Candidatus Pseudothioglobus . These groups are not normally associated with hydrocarbon biodegradation, despite closer inspection of genomes from closely related isolates confirming the potential for hydrocarbon metabolism. Co‐occurrence analysis further revealed significant associations between these genera and well‐known hydrocarbon‐degrading bacteria, suggesting potential synergistic interactions during oil biodegradation. While these findings broaden our understanding of how biostimulation promotes enrichment of endemic hydrocarbon‐degrading genera, further research is needed to fully assess the suitability of nutrient addition as a stand‐alone oil spill mitigation strategy in this sensitive and remote polar marine ecosystem.

P08-07 Prenatal developmental toxicity evaluation of higher olefins in Sprague-Dawley Rats - Q. Shi; J.-C. Carrillo; M. Penman; H. Shen; L. Kamelia; M. Rooseboom; S. Jia; J. Manton; F. Hubert; P. Boogaard (Toxicology Letters, 2024)

Immune cell profiles associated with human exposure to perfluorinated compounds (PFAS) suggest changes in natural killer, T helper, and T cytotoxic cell subpopulations - Amanda R. Tursi; Birgitte Lindeman; Anja Bråthen Kristoffersen; Hege Hjertholm; Eugenia Bronder; Monica Andreassen; Trine Husøy; Hubert Dirven; Sandra Andorf; Unni C. Nygaard (Environmental Research, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Enhancing biomass Pyrolysis: Predictive insights from process simulation integrated with interpretable Machine learning models - Douglas Chinenye Divine; Stell Hubert; Emmanuel I. Epelle; Alaba U. Ojo; Adekunle A. Adeleke; Chukwuma C. Ogbaga; Olugbenga Akande; Patrick U. Okoye; Adewale Giwa; Jude A. Okolie (Fuel, 2024)

Comparing open-source DEM frameworks for simulations of common bulk processes - M. Dosta; D. Andre; V. Angelidakis; R.A. Caulk; M.A. Celigueta; B. Chareyre; J.-F. Dietiker; J. Girardot; N. Govender; C. Hubert; R. Kobyłka; A.F. Moura; et al. (Computer Physics Communications, 2024)

Seasonality and lake water temperature inferred from the geochemistry and sclerochronology of quaternary freshwater bivalves from the Turkana Basin, Ethiopia and Kenya - Andrew S. Cohen; Julia Manobianco; David L. Dettman; Bryan A. Black; Catherine Beck; Craig S. Feibel; Josephine C. Joordens; Bert Van Bocxlaer; Hubert Vonhof (Quaternary Science Reviews, 2023)

The brightness of the CO Cameron bands in the martian discrete aurora: A study based on revised cross sections - J.-C. Gérard; L. Soret; B. Hubert; L. Neary; F. Daerden (Icarus, 2023)

Constraints for precise and accurate fluid inclusion stable isotope analysis using water-vapour saturated CRDS techniques - Therese Weissbach; Tobias Kluge; Stéphane Affolter; Markus C. Leuenberger; Hubert Vonhof; Dana F.C. Riechelmann; Jens Fohlmeister; Marie-Christin Juhl; Benedikt Hemmer; Yao Wu; Sophie F. Warken; Martina Schmidt; et al. (Chemical Geology, 2023)

Duration- and sex-dependent neural circuit control of voluntary physical activity - Margaret K. Tanner; Jazmyne K. P. Davis; Jennifer Jaime; Nicolette A. Moya; Alyssa A. Hohorst; Kelsey Bonar; Kelsey A. Abrams; Nashra Jamil; Rebecca Han; Troy J. Hubert; Nadja Brown; Esteban C. Loetz; et al. (Psychopharmacology, 2022)

A novel founder MSH2 deletion in Ethiopian Jews is mainly associated with early-onset colorectal cancer - I. Kedar; L. Walsh; G. Reznick Levi; S. Lieberman; A. Abu Shtaya; S. Naftaly Nathan; I. Lagovsky; R. Tomashov-Matar; M. Goldenberg; L. Basel-Salmon; L. Katz; O. Aleme; et al. (Familial Cancer, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Galactogenic plant diversity, phenology and local in situ conservation practices in agro-ecological zones of Benin Republic - Lucien Imorou; Euloge C. Togbé; Nicodeme V. Fassinou Hotegni; Daouda O. Bello; Bernice O. Biaou; Alexander T. K. Nuer; Hubert Adoukonou-Sagbadja; Léonard E. Ahoton (Genetic Resources and Crop Evolution, 2021)

Coping with Pleistocene climatic fluctuations: Demographic responses in remote endemic reef fishes - Erwan Delrieu‐Trottin; Nicolas Hubert; Emily C. Giles; Pascaline Chifflet‐Belle; Arnaud Suwalski; Valentina Neglia; Cristian Rapu‐Edmunds; Stefano Mona; Pablo Saenz‐Agudelo (Molecular Ecology, 2020)
Elucidating demographic history during the settlement of ecological communities is crucial for properly inferring the mechanisms that shape patterns of species diversity and their persistence through time. Here, we used genomic data and coalescent‐based approaches to elucidate for the first time the demographic dynamics associated with the settlement by endemic reef fish fauna of one of the most remote peripheral islands of the Pacific Ocean, Rapa Nui (Easter Island). We compared the demographic history of nine endemic species in order to explore their demographic responses to Pleistocene climatic fluctuations. We found that species endemic to Rapa Nui share a common demographic history, as signatures of population expansions were retrieved for almost all of the species studied here, and synchronous demographic expansions initiated during the last glacial period were recovered for more than half of the studied species. These results suggest that eustatic fluctuations associated with Milankovitch cycles have played a central role in species demographic histories and in the final stage of the community assembly of many Rapa Nui reef fishes. Specifically, sea level lowstands resulted in the maximum reef habitat extension for Rapa Nui endemic species; we discuss the potential role of seamounts in allowing endemic species to cope with Pleistocene climatic fluctuations, and we highlight the importance of local historical processes over regional ones. Overall, our results shed light on the mechanisms by which endemism arises and is maintained in peripheral reef fish fauna.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Guillain-Barré syndrome following varicella-zoster virus infection - Badrul Islam; Zhahirul Islam; Corine H. GeurtsvanKessel; Israt Jahan; Hubert P. Endtz; Quazi D. Mohammad; Bart C. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Transcriptional profiling by RNA sequencing of black pepper (Piper nigrum L.) roots infected by Fusarium solani f. sp. piperis - Edith C. O. Moreira; Daniel G. Pinheiro; Sheila M. C. Gordo; Simone M. Rodrigues; Elaine Pessoa; Hubert Schaller; Oriel F. de Lemos; Artur Silva; Horacio Schneider; Wilson A. Silva; Iracilda Sampaio; Sylvain Darnet (Acta Physiologiae Plantarum, 2017)

Reflections in the rainforest: full-length mirrors facilitate behavioral observations of unhabituated, wild chimpanzees - James R. Anderson; Xavier Hubert-Brierre; William C. McGrew (Primates, 2017)

Energy generation from domestic wastewater using sandwich dual-chamber microbial fuel cell with mesh current collector cathode - J. A. Adeniran; R. Huberts; J. J. De-Koker; O. A. Arotiba; O. F. Olorundare; E. Van-Zyl; S. C. Du-Plessis (International Journal of Environmental Science and Technology, 2016)

Effects of stress on AMPA receptor distribution and function in the basolateral amygdala - G. W. Hubert; C. Li; D. G. Rainnie; E. C. Muly (Brain Structure and Function, 2014)

Vulnerability of dynamic genetic conservation units of forest trees in Europe to climate change - Silvio Schueler; Wolfgang Falk; Jarkko Koskela; François Lefèvre; Michele Bozzano; Jason Hubert; Hojka Kraigher; Roman Longauer; Ditte C. Olrik (Global Change Biology, 2014)
A transnational network of genetic conservation units for forest trees was recently documented in Europe aiming at the conservation of evolutionary processes and the adaptive potential of natural or man‐made tree populations. In this study, we quantified the vulnerability of individual conservation units and the whole network to climate change using climate favourability models and the estimated velocity of climate change. Compared to the overall climate niche of the analysed target species populations at the warm and dry end of the species niche are underrepresented in the network. However, by 2100, target species in 33–65 % of conservation units, mostly located in southern Europe, will be at the limit or outside the species' current climatic niche as demonstrated by favourabilities below required model sensitivities of 95%. The highest average decrease in favourabilities throughout the network can be expected for coniferous trees although they are mainly occurring within units in mountainous landscapes for which we estimated lower velocities of change. Generally, the species‐specific estimates of favourabilities showed only low correlations to the velocity of climate change in individual units, indicating that both vulnerability measures should be considered for climate risk analysis. The variation in favourabilities among target species within the same conservation units is expected to increase with climate change and will likely require a prioritization among co‐occurring species. The present results suggest that there is a strong need to intensify monitoring efforts and to develop additional conservation measures for populations in the most vulnerable units. Also, our results call for continued transnational actions for genetic conservation of European forest trees, including the establishment of dynamic conservation populations outside the current species distribution ranges within European assisted migration schemes.

“Panta Rhei—Everything Flows”: Change in hydrology and society—The IAHS Scientific Decade 2013–2022 - A. Montanari; G. Young; H.H.G. Savenije; D. Hughes; T. Wagener; L.L. Ren; D. Koutsoyiannis; C. Cudennec; E. Toth; S. Grimaldi; G. Blöschl; M. Sivapalan; et al. (Hydrological Sciences Journal, 2013)

Adaptive genetic diversity of trees for forest conservation in a future climate: a case study on Norway spruce in Austria - Silvio Schueler; Stefan Kapeller; Heino Konrad; Thomas Geburek; Michael Mengl; Michele Bozzano; Jarkko Koskela; François Lefèvre; Jason Hubert; Hojka Kraigher; Roman Longauer; Ditte C. Olrik (Biodiversity and Conservation, 2013)

Dynamic Conservation of Forest Genetic Resources in 33 European Countries - FRANÇOIS LEFÈVRE; JARKKO KOSKELA; JASON HUBERT; HOJKA KRAIGHER; ROMAN LONGAUER; DITTE C. OLRIK; SILVIO SCHÜLER; MICHELE BOZZANO; PARASKEVI ALIZOTI; REMIGIJUS BAKYS; CATHLEEN BALDWIN; DALIBOR BALLIAN; et al. (Conservation Biology, 2013)
Dynamic conservation of forest genetic resources (FGR) means maintaining the genetic diversity of trees within an evolutionary process and allowing generation turnover in the forest. We assessed the network of forests areas managed for the dynamic conservation of FGR (conservation units) across Europe (33 countries). On the basis of information available in the European Information System on FGR (EUFGIS Portal), species distribution maps, and environmental stratification of the continent, we developed ecogeographic indicators, a marginality index, and demographic indicators to assess and monitor forest conservation efforts. The pan‐European network has 1967 conservation units, 2737 populations of target trees, and 86 species of target trees. We detected a poor coincidence between FGR conservation and other biodiversity conservation objectives within this network. We identified 2 complementary strategies: a species‐oriented strategy in which national conservation networks are specifically designed for key target species and a site‐oriented strategy in which multiple‐target units include so‐called secondary species conserved within a few sites. The network is highly unbalanced in terms of species representation, and 7 key target species are conserved in 60% of the conservation units. We performed specific gap analyses for 11 tree species, including assessment of ecogeographic, demographic, and genetic criteria. For each species, we identified gaps, particularly in the marginal parts of their distribution range, and found multiple redundant conservation units in other areas. The Mediterranean forests and to a lesser extent the boreal forests are underrepresented. Monitoring the conservation efficiency of each unit remains challenging; however, Conservación Dinámica de Recursos Genéticos Forestales en 33 Países Europeos

The role of Periodic Safety Update Reports in the safety management of biopharmaceuticals - Hans C. Ebbers; Aukje K. Mantel-Teeuwisse; Fakhredin A. Sayed-Tabatabaei; Ellen H. M. Moors; Huub Schellekens; Hubert G. M. Leufkens (European Journal of Clinical Pharmacology, 2013)

Active sulfur cycling by diverse mesophilic and thermophilic microorganisms in terrestrial mud volcanoes of A zerbaijan - A. Green‐Saxena; A. Feyzullayev; C. R. J. Hubert; J. Kallmeyer; M. Krueger; P. Sauer; H.‐M. Schulz; V. J. Orphan (Environmental Microbiology, 2012)
Summary Terrestrial mud volcanoes ( TMVs ) represent geochemically diverse habitats with varying sulfur sources and yet sulfur cycling in these environments remains largely unexplored. Here we characterized the sulfur‐metabolizing microorganisms and activity in four TMVs in A zerbaijan. A combination of geochemical analyses, biological rate measurements and molecular diversity surveys (targeting metabolic genes apr A and dsr A and SSU ribosomal RNA ) supported the presence of active sulfur‐oxidizing and sulfate‐reducing guilds in all four TMVs across a range of physiochemical conditions, with diversity of these guilds being unique to each TMV . The TMVs varied in potential sulfate reduction rates ( SRR ) by up to four orders of magnitude with highest SRR observed in sediments where in situ sulfate concentrations were highest. Maximum temperatures at which SRR were measured was 60° C in two TMVs . Corresponding with these trends in SRR , members of the potentially thermophilic, spore‐forming, D esulfotomaculum were detected in these TMVs by targeted 16 S rRNA analysis. Additional sulfate‐reducing bacterial lineages included members of the D esulfobacteraceae and D esulfobulbaceae detected by apr A and dsr A analyses and likely contributing to the mesophilic SRR measured. Phylotypes affiliated with sulfide‐oxidizing G amma ‐ and B etaproteobacteria were abundant in apr A libraries from low sulfate TMVs , while the highest sulfate TMV harboured 16 S rRNA phylotypes associated with sulfur‐oxidizing E psilonproteobacteria . Altogether, the biogeochemical and microbiological data indicate these unique terrestrial habitats support diverse active sulfur‐cycling microorganisms reflecting the in situ geochemical environment.

Sensitivity of coastal polynyas and high-salinity shelf water production in the Ross Sea, Antarctica, to the atmospheric forcing - Pierre Mathiot; Nicolas C. Jourdain; Bernard Barnier; Hubert Gallée; Jean Marc Molines; Julien Le Sommer; Thierry Penduff (Ocean Dynamics, 2012)

The quantitative significance of Syntrophaceae and syntrophic partnerships in methanogenic degradation of crude oil alkanes - N. D. Gray; A. Sherry; R. J. Grant; A. K. Rowan; C. R. J. Hubert; C. M. Callbeck; C. M. Aitken; D. M. Jones; J. J. Adams; S. R. Larter; I. M. Head (Environmental Microbiology, 2011)
Summary Libraries of 16S rRNA genes cloned from methanogenic oil degrading microcosms amended with North Sea crude oil and inoculated with estuarine sediment indicated that bacteria from the genera Smithella ( Deltaproteobacteria, Syntrophaceace ) and Marinobacter sp. ( Gammaproteobacteria ) were enriched during degradation. Growth yields and doubling times (36 days for both Smithella and Marinobacter ) were determined using qPCR and quantitative data on alkanes, which were the predominant hydrocarbons degraded. The growth yield of the Smithella sp. [0.020 g (cell‐C) /g (alkane‐C) ], assuming it utilized all alkanes removed was consistent with yields of bacteria that degrade hydrocarbons and other organic compounds in methanogenic consortia. Over 450 days of incubation predominance and exponential growth of Smithella was coincident with alkane removal and exponential accumulation of methane. This growth is consistent with Smithella's occurrence in near surface anoxic hydrocarbon degrading systems and their complete oxidation of crude oil alkanes to acetate and/or hydrogen in syntrophic partnership with methanogens in such systems. The calculated growth yield of the Marinobacter sp., assuming it grew on alkanes, was [0.0005 g (cell‐C) /g (alkane‐C) ] suggesting that it played a minor role in alkane degradation. The dominant methanogens were hydrogenotrophs ( Methanocalculus spp. from the Methanomicrobiales ). Enrichment of hydrogen‐oxidizing methanogens relative to acetoclastic methanogens was consistent with syntrophic acetate oxidation measured in methanogenic crude oil degrading enrichment cultures. qPCR of the Methanomicrobiales indicated growth characteristics consistent with measured rates of methane production and growth in partnership with Smithella .

Development and Experimental Validation of a 20K Atlantic Cod (Gadus morhua) Oligonucleotide Microarray Based on a Collection of over 150,000 ESTs - Marije Booman; Tudor Borza; Charles Y. Feng; Tiago S. Hori; Brent Higgins; Adrian Culf; Daniel Léger; Ian C. Chute; Anissa Belkaid; Marlies Rise; A. Kurt Gamperl; Sophie Hubert; et al. (Marine Biotechnology, 2011)

An Integrated Approach to Gene Discovery and Marker Development in Atlantic Cod (Gadus morhua) - Sharen Bowman; Sophie Hubert; Brent Higgins; Cynthia Stone; Jennifer Kimball; Tudor Borza; Jillian Tarrant Bussey; Gary Simpson; Catherine Kozera; Bruce A. Curtis; Jennifer R. Hall; Tiago S. Hori; et al. (Marine Biotechnology, 2011)

Influence of coupling on atmosphere, sea ice and ocean regional models in the Ross Sea sector, Antarctica - Nicolas C. Jourdain; Pierre Mathiot; Hubert Gallée; Bernard Barnier (Climate Dynamics, 2011)

Influence of the orographic roughness of glacier valleys across the Transantarctic Mountains in an atmospheric regional model - Nicolas C. Jourdain; Hubert Gallée (Climate Dynamics, 2011)

Regulatory scientific advice in drug development: does company size make a difference? - Michelle Putzeist; Aukje K. Mantel-Teeuwisse; Christine C. Gispen-De Wied; Arno W. Hoes; Hubert G. Leufkens (European Journal of Clinical Pharmacology, 2011)

Dose finding of melatonin for chronic idiopathic childhood sleep onset insomnia: an RCT - Ingeborg M. van Geijlswijk; Kristiaan B. van der Heijden; A. C. G. Egberts; Hubert P. L. M. Korzilius; Marcel G. Smits (Psychopharmacology, 2010)

Superior efficacy of new medicines? - Johan C. F. van Luijn; Frank W. J. Gribnau; Hubert G. M. Leufkens (European Journal of Clinical Pharmacology, 2010)

ABC Transporter Pdr10 Regulates the Membrane Microenvironment of Pdr12 in Saccharomyces cerevisiae - Nathan C. Rockwell; Hubert Wolfger; Karl Kuchler; Jeremy Thorner (The Journal of Membrane Biology, 2009)

Validation of a food frequency questionnaire measurement of dietary acrylamide intake using hemoglobin adducts of acrylamide and glycidamide - Kathryn M. Wilson; Hubert W. Vesper; Paula Tocco; Laura Sampson; Johan Rosén; Karl-Erik Hellenäs; Margareta Törnqvist; Walter C. Willett (Cancer Causes & Control, 2009)

Large scale purification protocol for carnocin KZ 213 from Carnobacterium piscicola - C. Saint-Hubert; A. Durieux; E. Bodo; J.-P. Simon (Biotechnology Letters, 2009)

Membrane perturbation by an external electric field: a mechanism to permit molecular uptake - J.-M. Escoffre; D. S. Dean; M. Hubert; M.-P. Rols; C. Favard (European Biophysics Journal, 2007)

Production of raw-starch-hydrolysing α-amylase from the newly isolated Geobacillus thermodenitrificans HRO10 - Thaddeus C. Ezeji; Hubert Bahl (World Journal of Microbiology and Biotechnology, 2007)

Recovery of Nuclease Produced by Lactococcus Lactis Using Expanded Bed Ion Exchange Chromatography - E. Bodo; A. Durieux; C. Saint-Hubert; R. Lavallée; J-M Boufflette; J. -P. Simon (Biotechnology Letters, 2006)

Concurrent assessment of fish and habitat in warmwater streams in Wyoming - M. C. QUIST; W. A. HUBERT; F. J. RAHEL (Fisheries Management and Ecology, 2006)
Fisheries research and management in North America have focused largely on sport fishes, but native non‐game fishes have attracted increased attention due to their declines. The Warmwater Stream Assessment (WSA) was developed to evaluate simultaneously both fish and habitat in Wyoming streams by a process that includes three major components: (1) stream‐reach selection and accumulation of existing information, (2) fish and habitat sampling and (3) summarisation and evaluation of fish and habitat information. Fish are sampled by electric fishing or seining and habitat is measured at reach and channel‐unit (i.e. pool, run, riffle, side channel, or backwater) scales. Fish and habitat data are subsequently summarised using a data‐matrix approach. Hierarchical decision trees are used to assess critical habitat requirements for each fish species expected or found in the reach. Combined measurements of available habitat and the ecology of individual species contribute to the evaluation of the observed fish assemblage. The WSA incorporates knowledge of the fish assemblage and habitat features to enable inferences of factors likely influencing both the fish assemblage and their habitat. The WSA was developed for warmwater streams in Wyoming, but its philosophy, process and conceptual basis may be applied to environmental assessments in other geographical areas.

Tryptophan hydroxylase 2 gene expression and promoter polymorphisms in bipolar disorder and schizophrenia - Vincenzo De Luca; Olga Likhodi; Hubert H. M. Van Tol; James L. Kennedy; Albert H. C. Wong (Psychopharmacology, 2005)

Constraints of body size and swimming velocity on the ability of juvenile rainbow trout to endure periods without food - D. G. Simpkins; W. A. Hubert; C. Martinez Del Rio; D. C. Rule (Journal of Fish Biology, 2004)
The hypothesis that body size and swimming velocity affect proximate body composition, wet mass and size‐selective mortality of fasted fish was evaluated using small (107 mm mean total length, L T ) and medium (168 mm mean L T ) juvenile rainbow trout Oncorhynchus mykiss that were sedentary or swimming ( c . 1 or 2 body length s −1 ) and fasted for 147 days. The initial amount of energy reserves in the bodies of fish varied with L T . Initially having less lipid mass and relatively higher mass‐specific metabolic rates caused small rainbow trout that were sedentary to die of starvation sooner and more frequently than medium‐length fish that were sedentary. Swimming at 2 body length s −1 slightly increased the rate of lipid catabolism relative to 1 body length s −1 , but did not increase the occurrence of mortality among medium fish. Death from starvation occurred when fish had

Genetic variations of KCNQ1, KCNH2, SCN5A, KCNE1 , and KCNE2 in drug-induced long QT syndrome patients - Aime D. C. Paulussen; Ronaldus A. H. J. Gilissen; Martin Armstrong; Pieter A. Doevendans; Peter Verhasselt; Hubert J. M. Smeets; Eric Schulze-Bahr; Wilhelm Haverkamp; Gnter Breithardt; Nadine Cohen; Jeroen Aerssens (Journal of Molecular Medicine, 2004)

Incidence and determinants of long-term use of antidepressants - Welmoed E. E. Meijer; E. R. Heerdink; Hubert G. M. Leufkens; Ron M. C. Herings; Antoine C. G. Egberts; Willem A. Nolen (European Journal of Clinical Pharmacology, 2004)

Small deletions disturb desmin architecture leading to breakdown of muscle cells and development of skeletal or cardioskeletal myopathy - Anna Kaminska; Sergei V. Strelkov; Bertrand Goudeau; Montse Oliv; Ayush Dagvadorj; Anna Fidzianska; Monique Simon-Casteras; Alexey Shatunov; Marinos C. Dalakas; Isidro Ferrer; Hubert Kwiecinski; Patrick Vicart; et al. (Human Genetics, 2004)

Nitrite reductase activity of sulphate‐reducing bacteria prevents their inhibition by nitrate‐reducing, sulphide‐oxidizing bacteria - E. A. Greene; C. Hubert; M. Nemati; G. E. Jenneman; G. Voordouw (Environmental Microbiology, 2003)
Summary Sulphate‐reducing bacteria (SRB) can be inhibited by nitrate‐reducing, sulphide‐oxidizing bacteria (NR‐SOB), despite the fact that these two groups are interdependent in many anaerobic environments. Practical applications of this inhibition include the reduction of sulphide concentrations in oil fields by nitrate injection. The NR‐SOB Thiomicrospira sp. strain CVO was found to oxidize up to 15 mM sulphide, considerably more than three other NR‐SOB strains that were tested. Sulphide oxidation increased the environmental redox potential (E h ) from −400 to +100 mV and gave 0.6 nitrite per nitrate reduced. Within the genus Desulfovibrio , strains Lac3 and Lac6 were inhibited by strain CVO and nitrate for the duration of the experiment, whereas inhibition of strains Lac15 and D. vulgaris Hildenborough was transient. The latter had very high nitrite reductase (Nrf) activity. Southern blotting with D. vulgaris nrf genes as a probe indicated the absence of homologous nrf genes from strains Lac3 and Lac6 and their presence in strain Lac15. With respect to SRB from other genera, inhibition of the known nitrite reducer Desulfobulbus propionicus by strain CVO and nitrate was transient, whereas inhibition of Desulfobacterium autotrophicum and Desulfobacter postgatei was long‐lasting. The results indicate that inhibition of SRB by NR‐SOB is caused by nitrite production. Nrf‐containing SRB can overcome this inhibition by further reducing nitrite to ammonia, preventing a stalling of the favourable metabolic interactions between these two bacterial groups. Nrf, which is widely distributed in SRB, can thus be regarded as a resistance factor that prevents the inhibition of dissimilatory sulphate reduction by nitrite.

Historical biogeography of Southeast Asia and the West Pacific, or the generality of unrooted area networks as historical biogeographic hypotheses - Peter C. van Welzen; Hubert Turner; Peter Hovenkamp (Journal of Biogeography, 2003)
Aim Unrooted area networks are perhaps a general way in which different historical biogeographical patterns may be combined. Location Southeast Asia up to the West Pacific, Australia, South America. Methods Unrooted area networks based on Primary Brooks Parsimony Analysis of different data sets of Southeast Asian–West Pacific, Australian and South American clades. Results A large Brooks Parsimony historical (cladistic) biogeographic analysis of Southeast Asia and the West Pacific gave a meaningful result when all clades (representing different historical biogeographic patterns) were united into one matrix and an unrooted area network was produced. This network showed geographically adjacent areas as neighbours, which is interpreted as clades dispersing and speciating as soon as areas rafted towards each other. This pseudo‐vicariance mechanism, together with the very limited, mainly linear dispersal possibilities, a few large, widespread clades with many endemic species, and the large overlap in distributions displayed by different patterns, may explain the peculiar result. When applied to examples from other areas (bird data from Australia and South America), unrooted area networks for all data perform very poorly. Main conclusions Unrooted historical general area networks are not universally applicable. In general, it is better to split historical patterns a priori and analyse them separately.

Environmental and Agricultural Literacy Education - D. Hubert; A. Frank; C. Igo (Water, Air, & Soil Pollution, 2000)

Abstracts - Gregor Anderluh; Ariana Barlič; Zdravko Podlesek; Gianfranco Menestrina; Peter Maček; Franc Gubenšek; Alioša Bavec; Blaž Cigiš; Matjaž Zorko; Alenka Čopič; Nataša Vučemilo; Igor Križaj; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Primordial germ cells of the rabbit are specifically recognized by a monoclonal antibody labelling the perimitochondrial cytoplasm - C. Viebahn; Andreas Miething; Hubert Wartenberg (Histochemistry and Cell Biology, 1997)

Tumour induction by transplacental infection with polyoma virus of the F1 generation of wistar rats - W. Verhagen; C. M. Hubert; E. Mohtaschem (Archives of Virology, 1993)

The incidence of potato viruses X, Y and S in the Chilota potato collection - C. Theoduloz; J. Sáez-Vásquez; F. Poblete; A. Contreras; E. Hubert; L. Meza-Basso (American Journal of Potato Research, 1992)

In situ studies on the breakdown ofNymphoides peltata (Gmel.) O. Kuntze (Menyanthaceae); Some methodological aspects of the litter bag technique - Th. C. M. Brock; C. A. M. Huijbregts; M. J. H. A. Steeg-Huberts; M. A. Vlassak (Aquatic Ecology, 1982)

Recruitment and food-retrieving behavior in Novomessor (Formicidae, Hymenoptera) - Bert Hlldobler; Robert C. Stanton; Hubert Markl (Behavioral Ecology and Sociobiology, 1978)